The effect of multimorbidity patterns on physical and cognitive function in diabetes patients: a longitudinal cohort of middle-aged and older adults in China - Zhou, Xieting; Qin, Juan-Juan; Li, Hang; Chen, Jiyu; Zhang, Qing; Ye, Xujun (Frontiers in Aging Neuroscience, 2024)
Background: The prevalence of diabetes has increased rapidly and comorbid chronic conditions are common among patients with diabetes. However, little is known about the pattern of multimorbidity in diabetes patients and the effect on physical and cognitive function. The aim of this study is to assess the disease clusters, and patterns of multimorbidity in diabetes patients using a novel Latent Class Analysis (LCA) approach in middle-aged and older adults, and explore the association of different clusters of multimorbidity in diabetes and physical and cognitive function. Methods: This national observational study included 1,985 diabetes patients from the 4 waves of China Health and Retirement Longitudinal Study (CHARLS) in 2011 to 2018. Thirteen chronic diseases were used in latent class analysis to identify the patterns of multimorbidity in diabetes, which span cardiovascular, physical, psychological and metabolic systems. Cognitive function is assessed via a structured questionnaire in three domains including memory, executive function, and orientation. Combining activities of daily living (ADL) with instrumental activities of daily living (IADL) to measure physical function. Linear mixed models and negative binomial regression models were conducted to analyze the association between patterns of multimorbidity in diabetes and cognitive function and disability, respectively. Results: A sample of the 1,985 patients with diabetes was identified, of which 1,889 (95.2%) had multimorbidity; their average age was 60.6 years (Standard Deviation (SD) = 9.5) and 53.1% were female. Three clusters were identified: ‘cardio-metabolic’ (n=972, 51.5%), ‘mental-dyslipidemia-arthritis’ (n=584, 30.9%) and ‘multisystem morbidity’ (n=333, 17.6%). Compared with diabetes alone, the class that had an increased association with global cognitive decline was the ‘multisystem morbidity’. All patterns of multimorbidity were associated with an increased risk of memory decline and disability, though the ‘multisystem morbidity’ group also had the strongest association, and presented a higher ADL-IADL disability (Ratio=4.22, 95%CI=2.52, 7.08) and memory Z scores decline (β=-0.322, 95%CI=-0.550, -0.095, P=0.0058). Conclusion: Significant longitudinal associations between different patterns of multimorbidity in diabetes patients and memory decline and disability were observed in this study. Future studies are needed to understand underlying mechanisms and common risk factors for multimorbidity in diabetes patients and to propose more effective treatments.